Optimizing blood utilization: insights from a tertiary care hospital in Hubballi, Northern Karnataka, India - Kanangot, Meenakshi; Revankar, Siddharth P.; Yevoor, Kavitha; Vernekar, Sunita S. (International Journal of Research in Medical Sciences, 2025)
Background: Blood transfusion is a cornerstone of modern medical care. With the shift from whole blood to component therapy, especially in resource-limited settings, optimizing blood utilization is essential to ensure availability, minimize wastage, and improve patient outcomes. Methods: To analyze the utilization patterns of blood and its components at a tertiary care center in Hubballi, Karnataka, over a three-year period, with an emphasis on usage trends, demographic distribution, and discard rates. A descriptive, observational study was conducted at the blood centre of Karnataka Medical College and Research Institute, Hubballi, India from January 2021 to December 2023. Data were extracted from blood bank records, including type of components used, patient demographics, clinical indications, and reasons for discards. Trends were compared with national and international studies. Results: A total of 45,514 units were collected, and 44,139 units utilized. Component therapy accounted for 78% of transfusions, with packed red blood cells (39%), fresh frozen plasma (29%), and platelets (10%). Whole blood usage remained at 22%. Female recipients constituted 57% of transfusions, primarily in reproductive age groups. The discard rate was 3.02%, mainly due to transfusion-transmitted infections and donor-related issues. Conclusion: The study highlights a favorable shift toward component therapy, though whole blood use still exceeds national benchmarks. Strengthening clinician awareness, donor screening, and inventory practices, along with regular audits, is vital for enhancing transfusion efficiency and safety.